Influencing factors on the psychosomatic health of medical staff since the normalized stage of COVID-19 in mainland China - Jiao, Xing-ai; Bai, Run-ai; Li, Na; Liu, Kao (European journal of public health, 2024)
Background During the coronavirus disease 2019 (COVID-19) pandemic, there were under-recognized and unaddressed psychosomatic health problems among medical staff. The purpose of this study was to investigate their psychosomatic status. Methods An online questionnaire was performed to the medical staff of major hospitals in Jinan in January 2023. In total, 1244 valid questionnaires were collected, and their psychosomatic status was assessed by the Psychosomatic Symptom Scale (PSSS) and Perceived Stress Scale-10 (PSS-10). Finally, we analyzed the influencing factors for their psychosomatic status. Results The psychological health of the medical staff was poor, and the level of stress perception was intense, accompanied by obvious psychosomatic symptoms. Regression analysis indicated that age, gender, frontline involvement, work experience, marriage, presence of disease history and COVID-19 infection history were risk factors for psychosomatic symptoms, while education, frontline involvement and presence of disease history were risk factors for stress feeling. Conclusion Medical staff often showed obvious psychosomatic symptoms and intense stress. Psychological health education and intervention should be given in order to improve their working quality.